A systematic review of iodine deficiency among women in the UK. Issue 6 (31st December 2018) - Jiang, Huiqing; Powers, Hilary J; Rossetto, Giulia S
Abstract: Objective: The present study reviewed the literature on iodine status among women of childbearing age and pregnant women in the UK. Particular attention was given to study quality and methods used to assess iodine status. Design: A systematic review was conducted to examine the literature and critically evaluate study design. Setting: Studies were identified in PubMed, Web of Science, Scopus and Ovid MEDLINE databases, as well as from secondary references. Participants: Women of childbearing age or pregnant, living in the UK. Results: Fifty-seven articles were identified and twelve articles were selected, including a total of 5283 women. Nine studies conducted urinary iodine assessments, three studies conducted dietary assessments only, and seven studies classified their target population as iodine deficient according to WHO criteria. Conclusions: No single study from the selected articles could produce nationally representative results regarding the prevalence of iodine deficiency among the female population in the UK. Consideration of the evidence as a whole suggests that women of childbearing age and pregnant women in the UK are generally iodine insufficient. Further large-scale research is required for more accurate and reliable evidence on iodine status in the UK.